HTA and innovative treatments evaluation: the case of metastatic castration-resistant prostate cancer - Bretoni A; Ferrario L; Foglia E (ClinicoEconomics and Outcomes Research, 2019)
Alberto Bretoni, Lucrezia Ferrario, Emanuela FogliaCentre for Health Economics, Social and Health Care Management, LIUC – Università Cattaneo, Castellanza, ItalyPurpose: To investigate the implications of the introduction of two hormonal therapies, abiraterone acetate + prednisone (AA+P) and enzalutamide (ENZA), for the treatment of naïve patients with metastatic castration-resistant prostate cancer (mCRPC) in the Italian setting.Methods: In 2017–2018, a Health Technology Assessment was conducted in Italy, considering the National Healthcare Service (NHS) perspective. Data were retrieved from literature evidence, economic evaluations, and qualitative questionnaires, considering the 9 EUnetHTA dimensions, and a final multi-criteria approach.Results: On the basis of mCRPC prevalence and incidence rates in Italy, the analysis considered 11,212 males eligible to either AA+P or ENZA treatments. Both drugs led to an improvement of the patients’ overall survival, with respect to the standard of care, composed of docetaxel chemotherapy. However, AA+P showed a higher rate of drug-related moderate adverse events and a monitoring activities incidence superior to ENZA (+70%, p-value=0.00), which led to a major resources absorption (€ 1,056.02 vs € 316.25, p-value=0.00), whereas ENZA showed a better cost-effectiveness average value (CEV: 54,586.12 vs 57,624.15). Economic savings ranging from 1.46% to 1.61% emerged for the NHS, as well as organizational advantages, with fewer minutes required for the mCRPC management (AA+P: 815 mins vs ENZA: 500 mins). According to experts’ perceptions, based on a 7-item Likert scale (ranging from −3 to +3), similar results emerged on ethical and social impact (ENZA: 1.35 vs AA+P: 1.48, p-value>0.05), and on legal dimension (ENZA: 0.67 vs AA+P: 0.67, p-value>0.05), since both drugs improved the patients’ quality of life and received approval for use. High-level perceptions related to ENZA adoption emerged with regard to equity (ENZA: 0.69 vs AA+P: 0.25, p-value<0.05), since it is cortisone-free. Multi-criteria approach analysis highlighted a higher score of ENZA than comparator (0.79 vs 0.60, p-value=0.00).Conclusion: The evidence-based information underlined the advantages of ENZA and AA+P treatments as therapeutic options for mCRPC patients. In the appraisal phase, the higher score than the comparator suggested ENZA as the preferred treatment for mCRPC.Keywords: mCRPC, multidimensional assessment, economic evaluation, decision analysis, hormonal therapies, MCDA